Establishment and characterization of a cell line (RBME-6) of Rhipicephalus (Boophilus) microplus from Brazil - Lima-Duarte, Leidiane; Camargo, Jaqueline Valéria [UNESP]; Castro-Santiago, Ana Carolina; Machado, Rosangela Zacarias [UNESP]; André, Marcos Rogério [UNESP]; Cabral-de-Mello, Diogo Cavalcanti [UNESP]; Camargo-Mathias, Maria Izabel [UNESP]; Ikeda, Priscila [UNESP]; Anholeto, Luís Adriano [UNESP]; Pereira, Melissa Carolina [UNESP]; da Costa, Alvimar José [UNESP]; Barros-Battesti, Darci Moraes [UNESP] (Elsevier, 2021)
Tick cell lines have already proved to be a useful tool for obtaining more information about possible vector species and the factors governing their ability to transmit a pathogen. Here, we established and characterized a cell line (RBME-6) derived from embryos of Rhipicephalus microplus from Brazil. Primary tick cell cultures were prepared in L-15B medium supplemented with 20% fetal bovine serum and 10% tryptose phosphate broth. The cell monolayers were subcultured when they reached a density of approximately 8 × 10 5 cells/mL (95% viability). Only after the sixth subculture were cells thawed from storage in liquid nitrogen successfully. Cytological analyses were performed using live phase contrast microscopy and cytocentrifuge smears stained with Giemsa, while periodic acid-Schiff and bromophenol blue staining techniques were used to detect total polysaccharides and total protein, respectively. No DNA from Anaplasma spp., Anaplasma marginale, Babesia spp., Bartonella spp., Coxiella spp., Ehrlichia canis, Rickettsia spp. or Mycoplasma spp. was detected in the cells through PCR assays. In addition, we performed chromosomal characterization of the tick cell line and confirmed the R. microplus origin of the cell line through conventional PCR and sequencing of a fragment of the mitochondrial 16S rRNA gene. In conclusion, we established and characterized a new cell line from a Brazilian population of R. microplus, which may form a useful tool for studying several aspects of ticks and tick-borne pathogens.
Keywords: Brazil; Cattle tick; Cell line; Chromosome